Song of solomon ebook - Morrison, Toni (2007)
NEW YORK TIMES BESTSELLER • An official Oprah Winfrey’s “The Books That Help Me Through” selection • The acclaimed Nobel Prize winner transfigures the coming-of-age story w ith this brilliantly imagined novel . Includes a new foreword by the author. One of The Atlantic ’s Great American Novels of the Past 100 Years Milkman Dead was born shortly after a neighborhood eccentric hurled himself off a rooftop in a vain attempt at flight. For the rest of his life he, too, will be trying to fly. As Morrison follows Milkman from his rustbelt city to the place of his family’s origins, she introduces an entire cast of strivers and seeresses, liars and assassins, the inhabitants of a fully realized Black world. “Morrison moves easily in and out of the lives and thoughts of her characters, luxuriating in the diversity of circumstances and personality, and revelling in the sound of their voices and of her own, which echoes and elaborates theirs.” — The New Yorker